Masonic Secrets in and Brown’s The Lost Symbol - Arahman, Fitrah Ningsih S (Journal of Comprehensive Science, 2024)
This research delves into the Masonic secrets embedded within Dan Brown's novel "The Lost Symbol," particularly as they relate to Washington D.C.'s enigmatic history. The study centers on Freemasonry symbols depicted in the novel and seeks to uncover their deeper meanings by analyzing real-life counterparts. The primary aim is to disclose the second-order meanings of these symbols, thereby unraveling the myths associated with Freemasonry, especially the so-called "lost symbol." Employing Roland Barthes' semiology perspective, this research reveals how Masonic symbols, as described by Brown, are interwoven with Washington's iconic monuments. The analysis focuses on symbols such as the House of the Temple, the Apotheosis of Washington, the Pyramid, the Circumpunct, and various Masonic working tools. By interpreting these symbols through both their first-order (denotative) and second-order (connotative) meanings, the study aims to reveal the myth behind the lost symbol. The findings indicate that the Masonic secrets are indeed hidden within the Washington Monument and the Capitol Building, specifically in the House of the Temple, where Masonic rituals are conducted, and the Capitol Rotunda, which is rich with concealed Masonic lore. The ultimate Masonic secret, as portrayed in the novel, is the "Lost Word," symbolized by the phrase "Laus Deo" (Praise God), inscribed atop the Capitol. According to Masonic beliefs, this symbol holds the power to unlock profound secrets, guiding them towards their ultimate objective: the establishment of a New World Order. Through the lens of second-order meaning, the myth of the lost word is interpreted as a celestial symbol, representing the promise of new beginnings and the transition from night to morning, as envisioned by the Masonic forefathers who designed the U.S. Capitol.